Illicit drugs in the Colombia-U.S. Relationship: Review and prospects (2015)
The chapter evaluates the U.S.-Colombian relationship regarding drug control policies. The first section of the work identifies the basic assumptions of the war on drugs, highlighting the trends of "American exceptionalism" and securitization in order to understand the types of policies Washington has adopted. The chapter assesses the results of the war on drugs and concludes with debates about drugs that have occurred within the U.S. in order to understand the current bilateral relations between Washington and Bogotá.